"Designing an ESP Course for the Construction Industry: A Workplace Communication Focus" (The Peerian Journal, 2025)
The Construction Industry English course is designed for construction industry workers employed by an international company. This course aims to improve their workplace communication skills, teaching them to effectively participate in meetings and presentations. In order to develop a proper course, Airport English by Joan Cutting was taken as a model framework from Part 3 of Woodrow (2018).